A hidden giant: Wallenberg syndrome and aortal wall thickening as an atypical presentation of a giant cell arteritis. (1st March 2013) - Stengl, Katharina Luisa; Buchert, Ralph; Bauknecht, Hans; Sobesky, Jan
Abstract : We report a case of a 73-year-old woman with a brainstem stroke presenting as Wallenberg syndrome. By transoesophageal echocardiography and combined 18F-fluordeoxyglucose positron emission and CT (18F-FDG PET/CT), the diagnosis of large artery vasculitis owing to giant cell arteritis was confirmed. In the absence of classical clinical signs, the examination of the large extracranial vessels by ultrasound and 18F-FDG PET/CT played the key role in detecting a widespread vasculitis.